Application Of Inverted Pendulum in Laplace Transformation of Mathematics Physics - Trisonia Fitria; Wipsar Sunu Brams Dwandaru; Warsono; R. Yosi Aprian Sari; Dian Puspita Eka Putri; Adiella Zakky Juneid (Jurnal Penelitian Pendidikan IPA, 2023)
The Laplace transform is a technique used to convert differential equations into algebra, it is often used for the analysis of dynamic systems and inverted pendulum systems. An inverted pendulum is a mechanism that moves objects from one place to another and shows the function of its activity while walking. This system is widely used in various fields, for example in the fields of robotics, industry, technology and organics. In an inverted pendulum there is an inverted pendulum dynamic system with a reading and driving force. The type of research used is pure research with quantitative methods, the aim is to develop science that aims to find new theories and develop existing theories in natural science. The results of the study show that using the Laplace transform can make it easier to find solutions regarding the inverted pendulum system for a variety of conditions, both in the initial conditions and when given an additional force or load, so it is concluded the application of the Laplace transform is useful for understanding how an inverted pendulum system will react to various forces, loads and initial conditions, which can be used to predict how the system will operate in the real world.